Best practices for velocity estimations in highly aerated flows with dual-tip phase-detection probes. (May 2020) - Kramer, M.; Hohermuth, B.; Valero, D.; Felder, S.
Highlights: Presentation of AWCC technique and selection of AWCC processing parameters. Estimation of pseudo instantaneous velocities in turbulent air-water flows. Robust calculation of turbulence intensities and extrapolation to single particle values. Comparison with conventional signal processing methods shows advantages of AWCC. Best practices recommendations for application of AWCC in turbulent airwater flows. Abstract: Dual-tip phase-detection probes can be used to measure flow properties in gas-liquid flows. Traditionally, time-averaged interfacial velocities have been obtained through cross-correlation analysis of long time-series of phase fraction signals. Using small groups of detected particles, a recently developed adaptive window cross-correlation (AWCC) technique enables the computation of pseudo-instantaneous interfacial velocities and turbulence quantities in highly aerated flows, albeit subject to some smoothing which is due to the use of a finite window duration. This manuscript provides guidance on the selection of optimum processing parameters for the AWCC technique, additionally addressing shortcomings such as velocity bias correction and extrapolation of turbulence levels to single particles. The presented technique was tested for three self-aerated flows: smooth and rough-wall boundary layers (tunnel chute and stepped spillway), as well as breaking shear layer flows of a hydraulic jump. Robust estimations of mean velocities and velocity fluctuations were obtained for all flow situations, either using dual-tip conductivity or fiber optical probe data. The computation of integral time scales and velocity spectra is currently limited by the data rate and must be treated with caution.